Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.8994
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 functions as a molecular rheostat to control the growth, tumorigenicity and drug responses of pancreatic ductal adenocarcinoma cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly deadly malignancy. Expression of the stem cell transcription factor SOX2 increases during progression of PDAC. Knockdown of SOX2 in PDAC cell lines decreases growth in vitro; whereas, stable overexpression of SOX2 in one PDAC cell line reportedly increases growth in vitro. Here, we reexamined the role of SOX2 in PDAC cells, because inducible SOX2 overexpression in other tumor cell types inhibits growth. In this study, four PDAC cell lines were engineered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 67 publications
(84 reference statements)
9
49
0
Order By: Relevance
“…SOX2 expression predicts poor survival of HCC patients and it promotes liver cancer cell invasion by activating Slug (24). In pancreatic ductal adenocarcinoma cells, SOX2 functions as a molecular rheostat to control the growth, tumorigenicity and drug response (29). Moreover, Li et al demonstrated that SOX2 could promote tumor metastasis by stimulating epithelial-to-mesenchymal transition via regulation of Wnt/β-catenin signal pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 expression predicts poor survival of HCC patients and it promotes liver cancer cell invasion by activating Slug (24). In pancreatic ductal adenocarcinoma cells, SOX2 functions as a molecular rheostat to control the growth, tumorigenicity and drug response (29). Moreover, Li et al demonstrated that SOX2 could promote tumor metastasis by stimulating epithelial-to-mesenchymal transition via regulation of Wnt/β-catenin signal pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that exogenous elevation of SOX2 can promote resistance to chemotherapeutics currently being used clinically [ 29 , 34 , 38 , 48 , 49 , 67 , 75 , 80 , 111 114 ]. In a report from Bareiss et al, ovarian cancer cell lines that did not express SOX2 and that were sensitive to carboplatin, cisplatin, and paclitaxel became resistant following stable, ectopic expression of SOX2 [ 80 ].…”
Section: Expression and Function Of Sox2 In Cancermentioning
confidence: 99%
“…Furthermore, it has been shown that inducible-overexpression and inducible-knockdown of SOX2 in PDAC cell lines altered responses to small molecule inhibitors targeting MEK and AKT signaling. In this study, overexpression of SOX2 protected PDAC cells from the growth inhibitory effects of MEK and AKT inhibitors; whereas, knocking down SOX2 enhanced the growth inhibition in the presence of these drugs [ 114 ]. While SOX2 may be acting to protect tumor cells through antiapoptotic signaling or quiescent-like phenotypes [ 29 , 37 , 67 , 75 ], SOX2 may also be promoting drug resistance through various ATP-binding cassette (ABC) transporters, including ABCG2, ABCC3, and ABCC6.…”
Section: Expression and Function Of Sox2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that overexpression of SOX2 contributes to resistance of MCF-7 breast cancer cells to tamoxifen, whereas downregulation of SOX2 enhanced the sensitivity of MCF-7 cells to tamoxifen (17). In addition, it was found that knockdown of SOX2 in pancreatic ductal adenocarcinoma cells increased the response to small-molecule inhibitors targeting MEK and AKT signaling (18). A recent study indicated that down regulation of SOX2 reduced invasiveness and increased sensitivity to paclitaxel by preserving the epithelial-like properties of breast cancer stem cells (19).…”
Section: Introductionmentioning
confidence: 99%